Contemporary Vietnamese fiction written about the war from the gender perspective - Anh, Thai Phan Vang (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2016)
The nature of every war is the same, whether in Asian countries, in Vietnam or anywhere else. However, in reality and literature, war always brings many faces, depending on which aspects and which perspectives it is seen and explained. From the gender perspective, we believe that under a certain aspect “a war has a female face”. Contemporary Vietnamese fiction describes war from the view of “feminine disposition”, realizes women’s beauty during and after war and condemns the brutal destruction of war from the fate of women. From the feminist perspective on war, contemporary Vietnamese fiction also mentions the instinctive desire, the desire to be loved, to be a wife, a mother of women; as well as condemns sexual prejudices to women.